2018
DOI: 10.1108/jfc-01-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Corruption in the Nigeria Judicial System: An Overview

Abstract: Purpose The purpose of this study is to examine corruption in the Nigeria judicial system, the implications on justice administration and the fight against corruption in the country, and proffer recommendations on ways to eradicate corruption in the system. Design/methodology/approach This paper is essentially a desk research with reliance on secondary source of data in published outlets such as journal articles, online articles and books. Findings There is prevalence of corruption in the judicial system, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…We agree with Lambsdorff because public-sector employees in Nigeria and many developing countries appear to be generally underpaid compared to their counterparts in the private sector and so, they may be more susceptible to engaging in unethical acts to supplement their salaries. Our findings also agree with Roozen et al (2001) and Sardžoska and Tang (2009), who argued that employees would differ in their EDM process based on the sector of the organisation where they work. We, therefore, understand that work sector is one of the background factors influencing accountants’ EDM process when faced with situations involving ethical dilemmas.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We agree with Lambsdorff because public-sector employees in Nigeria and many developing countries appear to be generally underpaid compared to their counterparts in the private sector and so, they may be more susceptible to engaging in unethical acts to supplement their salaries. Our findings also agree with Roozen et al (2001) and Sardžoska and Tang (2009), who argued that employees would differ in their EDM process based on the sector of the organisation where they work. We, therefore, understand that work sector is one of the background factors influencing accountants’ EDM process when faced with situations involving ethical dilemmas.…”
Section: Discussionsupporting
confidence: 91%
“…The results also showed no significant difference in the ethical responses between managers in public organisations and those in private organisations. In examining behavioural intentions of managers in the private and public sectors of the Republic of Macedonia, Sardžoska and Tang (2009) found that managers in the private sector had higher corporate ethical values, lower unethical behaviour intentions, lower irritation and higher life satisfaction than those in the public sector. The study further showed no difference in the love of money between managers in the private and in the public sectors.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, much corruption may be prevented by strong institutions; especially with cooperation from the private sector in ceasing to issue bribes (World Bank, 2018). The current fight against corruption in Nigeria has also not yielded meaningful results, due to lack of complementary support from the judiciary (Salihu & Gholami, 2019). Moreover, the extent to which the level of corruption control influences corporate sustainability disclosure compliance (CSDC) with the Nigerian CG code is yet to be ascertained by researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, lengthy and troublesome bottlenecks shape these incentives in the name of administrative due process. As a result, corruption has become not just endemic but also prevalent, acceptable, and the norm in Nigeria (Salihu & Gholami, 2018).…”
Section: Similarly Stanbic Bank Assistance Manager Acknowledged Thatmentioning
confidence: 99%